Comparative histopathological and immunological study of two field strains of chicken anemia virus - Rimondi, Agustina (2014)
Infection of poultry with chicken anemia virus (CAV) is implicated in several field problems in broiler flocks due to the immunosuppression generated and, consequently, the increased susceptibility to secondary infections. Recently, we have reported an increased occurrence of clinical cases caused by CAV strains distantly related to those commonly used for vaccination. In order to understand the behavior of two Argentinean CAV strains (CAV-10 and CAV-18) in two-week-old chickens, an immune and histopathological study was performed. Neither mortality nor clinical signs were observed in the infected or control groups. Thymus lobes from chickens infected with both CAV viruses were smaller compared to the negative control group. At 14 days post-infection (dpi), only chickens inoculated with CAV-10 show a severe depletion of lymphocytes in the thymus cortex and in follicles from the bursa of Fabricius. Also thymopoiesis disorders, such as reduction in the percentage of total DP (CD4 + CD8α+) thymocytes and alteration in the percentages of DP subpopulations, were more important in animals inoculated with the CAV-10 than the CAV-18 strain. In addition, only animals infected with CAV-10 show a decrease in CD8αβ splenocytes. Altogether our results show that, although both Argentinean CAV strains produce subclinical infections in chickens causing immunosuppression at 14 dpi, they might differ in their in vivo pathogenicity.